CLIMATE CHANGE AND COMMUNITY ENVIRONMENTAL CONFLICTS: ARE THEY CORRELATED? - Achmad Romsan; Farida Ali; Akhmad Idris; Adrian Nugraha; Nurhidayatuloh Nurhidayatuloh; Suzanna Mohamed Isa (Faculty of Law, Sriwijaya University, Indonesia, 2017)
Climate change and global warming affect major change in freshwater availability and season uncertainty which hamper all part of the globe. Although the phenomenon is not new but it needs concerns from all the government of States around the world to address the problem. If notthe drought and water shortages will directly and indirectly be the world problem and finally will ignite conflict over resources.Pollution and environmental degradation will also affect the sustainability of community’s economic activities. In Indonesia, since the enforcement of the first Environmental Management Act of 1982 up to the third Environmental Management Act of 2019, there have been forty one conflicts involving community and industries and palm plantation companies. All the conflicts are brought before the courts. Herein, industries and plantations are blamed for responsible for river water pollution and environmental degradation. Unfortunately, there is very little information in Indonesia obtained from the research reports, journals, news papers, magazines whether climate change and global warming also responsible for the occurrence of community environmental conflict. From the second data sources obtained from outsite Indonesia it is found that there is a link between climate change and community environmental disputes. The objectives of this paper tryto examine whether the cases submitted and solved by the District Courtsalso have some connection with the climate change phenomenon. Other objectives are to recommend to the Government of Indonesia to strengthen the existing regulations dealing with the climate change